PEMBERDAYAAN EKONOMI KELUARGA MELALUI PELATIHAN PEMBUATAN SIRUP JAHE SERAI DI DESA BEDAH LAWAK - Zulfikar; Agus Suhadi; , Denmas Amirul Haq; Khusni Wildani; Sampurna Kabir By khoir (Asosiasi Dosen Akutansi Indonesia, KEPRI, 2022)
Bedah Lawak village has a quite good potential to be developed as a processed ingredient for healthy drinks, especially from ginger and lemongrass plants. These two plants are often found and often wasted. Based on these opportunities, it is necessary to empower the family economy by conducting training on making healthy lemongrass ginger syrup. This community service activity is carried out to take advantage of the potential of housewives to earn additional income to support the family economy, and improve the economy/family welfare using the Community Based Research (CBR) method approach. The implementation of community service is carried out through training and assistance in the process of making syrup drink products, as well as product marketing techniques facilitated by village officials. The results of this activity resulted in a healthy drink product with the Perfectly Healthy Ginger (JSS) brand packaged in a plastic bottle so that this product is ready to be marketed and able to provide additional income for housewives.